2013
DOI: 10.5455/2320-1770.ijrcog20131233
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcome in patients of heart failure at a tertiary care centre

Abstract: Background: To study maternal and fetal outcome in antenatal patients with heart failure. Methods: The present study was conducted on pregnant female with heart failure admitted to hospital UISEMH, Kanpur from January 2012 to August, 2013. We attended 6800 pregnant female admitted to hospital out of which 48 pregnant female had heart failure during pregnancy or in labour. This was descriptive observational study. Results: Percentage of pregnant female with heart failure in our study was 0.7%. The mean of age d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 5 publications
1
16
2
Order By: Relevance
“…Morsheda Banu et al; in assessing showed that overall age distribution in majority (74%) of the respondents were between 20-35 years. 13 In present study, majority of patients were primigravida (46%), which is comparable. 14 Morsheda Banu et al; had found that around 50% of the women were primigravida.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Morsheda Banu et al; in assessing showed that overall age distribution in majority (74%) of the respondents were between 20-35 years. 13 In present study, majority of patients were primigravida (46%), which is comparable. 14 Morsheda Banu et al; had found that around 50% of the women were primigravida.…”
supporting
confidence: 72%
“…The commonest indication of caesarean section amongst referred patients was fetal distress. 13,19 Sorbye et al found that referral status contributed substantially to the increased caesarean section rate, which was 55% in formally referred. 20 In present study, 39% referred cases underwent caesarean section so we can conclude that rate of caesarean section is substantially high in referred cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 56%, 30% and 14% of cases were referred to our hospital in their intrapartum, antepartum and postpartum period respectively. Similar results were found by Devineni K et al 14 in their "Study of spectrum of referral pattern at a tertiary teaching hospital towards better obstetric care".…”
mentioning
confidence: 99%
“…13,18 The patients with previous caesarean section are referred to higher centres from PHC/CHC due to unavailability of operation theatre, gynaecologists, anaesthetics, trained staff or basic infrastructure deficits.…”
mentioning
confidence: 99%